Kazenskopravno varstvo človekovih pravic in svoboščin - Ferlinc, Andrej (Pravnik, 2016)
The comparative law makes observations on whether it is possible to give some answers about the appropriateness from criminal policy perspective with regard to the scheme and completeness of the criminal legal protection of human rights and freedoms. In this aspect, the author recalls the constitutional principle of equality before the law and his reflection in criminal law jurisdictions. He separately deals with different types of violence and agrees with the Italian model about incrimination of complete dependence and subjugation. In the area of privacy protection and other areas of human right protection the author agrees with the Italian model practices taking into account the greater potential unlawful interference with privacy due to the development of information technologies.
Keywords: človekove pravice; human rights; Italija; Italy; kazniva dejanja; kršenje; pravno varstvo; preprečevanje; Slovenia; Slovenija